IS FREEDOM OF EXPRESSION IN DANGER IN THE LIGHT OF THE CJEU DECISIONS ON THE CASES C-507-17 GOOGLE V. CNIL AND C-18/18 EVA GLAWISCHNIG- PIESCZEK V. FACEBOOK? - Feyza Basar, Feyza Basar (Актуальні проблеми правознавства, 2021)
Last year in September and November, the Court of Justice of the European Union (CJEU) rendered two important judgements on landmark cases C-507/17 Google v. Commission nationale de L’informatique et des libertes (CNIL) (24 September 2019) and C-18/18 Eva Glawischnig- Piesczek v. Facebook Ireland Limited  (G-P v. Facebook) (3 October 2019). At first sight, these cases do not directly related to those fundamental rights as they are more about personal, material and territorial limits on the scope of right to be forgotten (Google v. CNIL) or an injunction (G-P v. Facebook). However they, especially the second judgement, will have serious effect on freedom of expression and access to information. In Google v. CNIL, the CJEU ruled that French national data protection authority’s order demanding that Google remove certain offending search results worldwide was impermissible. On the other hand, in G-P v. Facebook, the Court held that Article 15 of the EU’s e-commerce directive does not prohibit EU Member States from ordering extremely broad injunctions against platforms like Facebook to take down offending material (and therefore allows it). The court held that these injunctions can cover a wide array of material-not just Facebook posts but also reposts and “equivalent” posts- and apply worldwide. In this study, the limits to the freedom of expression and access to information shall be analysed under the case law of the ECtHR and CJEU with specific evaluation as the possible consequences of Google and Facebook judgements rendered by the CJEU.